Analisis Dana Alokasi Umum dan Khusus Terhadap Belanja Daerah pada Badan Pengelolaan Keuangan dan Pendapatan Daerah Kabupaten Kebumen - Suratno Suratno (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The purpose of the study is to analyze the General Allocation Funds and Special Allocation Funds for Regional Expenditures at BPKPD Kebumen Regency. This research method uses a descriptive reseach method with a quantitative approach. Data analysis techniques for General Allocation Funds for Regional Expenditures, namely dividing General Allocation Funds with Regional Expenditures multiplied by 100% and Special Allocation Funds for Regional Expenditures, namely dividing Special Allocation Fund with Regional Expenditures multiplied by 100%. The result of this study indicate that General Allocation Fund for Regional Expenditures in 2019-2021 is included in good criteria, namely in 2019 45,35% with “good” criteria, in 2020 41,55% “good” criteria, and in 2021 40% criteria “currently”. Meanwhile, the Special Allocation Fund for Regional Expenditures fro 2019-2021 is included in the very lucking criteria, namely in 2019 it is 2,56% of the “very lucking” criteria, in 2020 2,30% of the “very lucking” criteria, and in 2021 it is 2,56% “very less”.